2020
DOI: 10.3390/ijerph18010225
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Challenges in Rare Bleeding Disorders: FVIII Inhibitor Incidence in Haemophilia A Patients—A Known Issue of Unknown Origin

Abstract: There is a broad range of factor products approved in Germany for haemophilia A treatment. Since the introduction of recombinant coagulation factor VIII (FVIII) products in the 1990s, there has been substantial debate whether there is a difference in inhibitor incidence between single FVIII products or product classes. Neither haemophilia registries nor clinical studies, including a randomised controlled clinical trial, provided a consistent and definite answer. The reasons were mainly related to methodologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Although the preference for plasma-derived or recombinant FVIII products has been highly debated, mainly regarding the risk of inhibitor appearance, 260–262 both proved efficacious for preventing/treating bleeding episodes in haemophilia patients and the WFH recommendations do not express a preference for either recombinant or plasma-derived products 245,257 . However, the SIPPET randomised trial showed an increase in the inhibitor rate in patients using recombinant FVIII products compared with those receiving plasma-derived products in the first exposure days 263 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the preference for plasma-derived or recombinant FVIII products has been highly debated, mainly regarding the risk of inhibitor appearance, 260–262 both proved efficacious for preventing/treating bleeding episodes in haemophilia patients and the WFH recommendations do not express a preference for either recombinant or plasma-derived products 245,257 . However, the SIPPET randomised trial showed an increase in the inhibitor rate in patients using recombinant FVIII products compared with those receiving plasma-derived products in the first exposure days 263 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, 60% of trough and steady-state FIX levels were below the target level in the first 24 h after surgery, whereas 59% of FIX levels were above target more than 6 days after surgery, supporting the need for alternative dosing strategies such as pharmacokinetic monitoring. 259 Although the preference for plasma-derived or recombinant FVIII products has been highly debated, mainly regarding the risk of inhibitor appearance, [260][261][262] both proved efficacious for preventing/treating bleeding episodes in haemophilia patients and the WFH recommendations do not express a preference for either recombinant or plasma-derived products. 245,257 However, the SIPPET randomised trial showed an increase in the inhibitor rate in patients using recombinant FVIII products compared with those receiving plasma-derived products in the first exposure days.…”
Section: Evidence Summarymentioning
confidence: 99%
“…Эти антитела нейтрализуют гемостатический эффект введенного фактора, что приводит к рецидивирующим эпизодам кровотечения, прогрессирующему повреждению суставов и иногда к угрожающим жизни неотложным состояниям [3]. Возможная роль, которую играют факторы риска в развитии ингибиторов, такие как характер генетических нарушений [4], возраст начала лечения [5], выбор первого лекарственного препарата, режим и интенсивность введения [6], является предметом длительной дискуссии. Дополнительные факторы риска, такие как массивность кровотечения, хирургическое вмешательство [7], сопутствующие инфекции или вакцинации [8], также вовлечены в контекст обсуждения сигналов иммунологической опасности [9], приводящих к иммунным нарушениям, связанным с введением экзогенного фактора свертывания крови для остановки кровотечения.…”
Section: Abstract: Children Hemophilia a Risk Factors Clotting Inhibi...unclassified
“…Haemophilia is a rare X-linked inherited bleeding disorder characterised by remarkable management progress in the past several decades. Advances in novel haemophilia therapy development have primarily been driven by the efforts to address the many currently unmet needs in haemophilia care, which include the high disease and treatment burden (1-3), the need for intravenous infusion of factor replacement therapy (4)(5)(6)(7)(8), the immunogenicity of factor replacement therapy (9)(10)(11), suboptimal prophylaxis due to poor compliance and adherence (12). The non-factor replacement therapies (NFRT) ware developed to address some of these unmet needs in haemophilia care.…”
Section: Introductionmentioning
confidence: 99%